Chimpanzee Behavior in the Wild An Audio-Visual Encyclopedia - Nishida, Toshisada; Zamma, Koichiro; Matsusaka, Takahisa; Inaba, Agumi; McGrew, William C.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2010)
The behavior of chimpanzees is complex and challenging: they can be cheerful, curious, and tolerant while also being capable of cunning, greed, and violence. Until now, there has been no comprehensive glossary with illustrations upon which systematic behavioral comparisons could be based. Combining recent video footage with decades$1 (Bworth of documented across- and within-population variations in behavior, this volume is the first to compile an extensive ethogram of a single species of mammal. The wild chimpanzees of the Mahale Mountains and Gombe National Park, Tanzania, have been observed in particular, as well as those at other long-term fields in equatorial Africa. The book describes all aspects of chimpanzee behavior patterns, from locomotion and posture to feeding, facial expression, gestures, grooming, and vocal communication.s
Color Plates -- Methods -- Study Sites of Chimpanzees and Bonobos -- Catalogue -- Remarks -- Glossary A-F -- Glossary G-Q -- Glossary R-Y -- Discussion.
Keywords: Life sciences; Zoology; Life Sciences; Zoology